2012
DOI: 10.1186/1477-7819-10-181
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with the mTOR inhibitor everolimus in a patient with Perivascular epithelioid cell tumor

Abstract: Perivascular epithelioid cell tumor (PEComa) is an extremely rare neoplasm that appears to arise most commonly at visceral (especially gastrointestinal and uterine), retroperitoneal, and abdominopelvic sites. Malignant PEComas exist but are very rare. These tumors represent a family of mesenchymal neoplasms, mechanistically linked through activation of the mTOR signaling pathway. Metastatic PEComa is a rare form of sarcoma for which no effective therapy has been described previously and that has a uniformly fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 12 publications
(14 reference statements)
1
46
0
Order By: Relevance
“…There is sparse data on the cytogenetic and molecular genetics of sporadic PEComas, and the little data available is inconsistent. The evidence for the use of mTOR inhibitors stemmed from data showing increased markers of mTOC1 suggestive of loss of TSC1 or TSC2 [12].Good therapeutic response to mTOR inhibitors has been reported by Gennatas et al [5] offers a reasonable rationale for the initiation of this therapy [5]. Our Patient also demonstrated a reasonable degree of radiological response with mTOR inhibitor Evrolimus 10mg / day, our patient showed striking improvement in symptoms such as pain control, and improvement in appetite.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There is sparse data on the cytogenetic and molecular genetics of sporadic PEComas, and the little data available is inconsistent. The evidence for the use of mTOR inhibitors stemmed from data showing increased markers of mTOC1 suggestive of loss of TSC1 or TSC2 [12].Good therapeutic response to mTOR inhibitors has been reported by Gennatas et al [5] offers a reasonable rationale for the initiation of this therapy [5]. Our Patient also demonstrated a reasonable degree of radiological response with mTOR inhibitor Evrolimus 10mg / day, our patient showed striking improvement in symptoms such as pain control, and improvement in appetite.…”
Section: Discussionsupporting
confidence: 65%
“…She was subsequently therefore switched to mToR (mammalian target of Rapamycin) inhibitor Evrolimus [5].She showed a good clinical response with improvement in appetite, reduction in pain and requirement of analgesia, better performance status and feeling of general wellbeing. A repeat CT scan after 4 months of treatment revealed that the mass showed reduction in size and there were prominent necrotic appearing areas.…”
Section: Case Presentationmentioning
confidence: 99%
“…Treatment with everolimus was reported in two cases only: As a neoadjuvant treatment in 1 patient with primary liver PEComa, which lead to a good partial response allowing the patient to undergo surgery (7); and in 1 patient with primary retroperitoneal PEComa that had metastasized to the lungs, which lead to a complete response in the lung lesions and a partial response in the abdominal mass (12). In the current case, treatment with everolimus lead to stable disease in the patient for 18 months, with symptomatic relief and improvement in the quality of life of the patient for a disease that had rapidly progressed prior to this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a lack of regulation of cell proliferation, migration and differentiation (6). Since 2007, several cases of treatment with mTOR inhibitors in advanced PEComa have been described (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Significant clinical response with an oral mTOR inhibitor, everolimus, has been demonstrated in a patient with metastatic retroperitoneal angiomyolipoma. 23 Adjuvant interferon a immunotherapy has been given to a pediatric patient with PEComa of the ascending colon following surgery, with a good clinical outcome. 8 Many thanks to Travis Ogilvie, MD, at the Foothills Medical Centre (Calgary, Alberta, Canada) for intradepartmental consultation, and John Goldblum, MD, at the Cleveland Clinic (Cleveland, Ohio) for external consultation.…”
Section: Microscopic Examinationmentioning
confidence: 99%